Dynamics of Antibody Responses after Asymptomatic and Mild to Moderate SARS-CoV-2 Infections: Real-World Data in a Resource-Limited Country - Naruemit Sayabovorn; Pochamana Phisalprapa; Weerachai Srivanichakorn; Thanet Chaisathaphol; Chaiwat Washirasaksiri; Tullaya Sitasuwan; Rungsima Tinmanee; Chayanis Kositamongkol; Pongpol Nimitpunya; Euarat Mepramoon; Pinyapat Ariyakunaphan; Diana Woradetsittichai; et al. (Tropical Medicine and Infectious Disease, 2023)
The dynamics of humoral immune responses of patients after SARS-CoV-2 infection is unclear. This study prospectively observed changes in anti-receptor binding domain immunoglobulin G (anti-RBD IgG) and neutralizing antibodies against the Wuhan and Delta strains at 1, 3, and 6 months postinfection between October 2021 and May 2022. Demographic data, clinical characteristics, baseline parameters, and blood samples of participants were collected. Of 5059 SARS-CoV-2 infected adult patients, only 600 underwent assessment at least once between 3 and 6 months after symptom onset. Patients were categorized as immunocompetent (n = 566), immunocompromised (n = 14), or reinfected (n = 20). A booster dose of a COVID-19 vaccine was strongly associated with maintained or increased COVID-19 antibody levels. The booster dose was also more strongly associated with antibody responses than the primary vaccination series. Among patients receiving a booster dose of a mRNA vaccine or a heterologous regimen, antibody levels remained steady or even increased for 3 to 6 months after symptom onset compared with inactivated or viral vector vaccines. There was a strong correlation between anti-RBD IgG and neutralizing antibodies against the Delta variant. This study is relevant to resource-limited countries for administering COVID-19 vaccines 3 to 6 months after infection.